Role and Position of Public Debt in Islamic Fiscal Policy in Indonesia - Roisatun Kasanah; Muhamad Nafik Hadi Ryandono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This study tries to provide an overview of the role and position of public debt in Islamic fiscal policy by collecting information from books, journals, scientific articles and official news related to fiscal policy in Indonesia. From the results of the analysis, the researcher found that although there are several opinions that suggest the use of public debt is permissible in overcoming the budget deficit that occurs in the state, there are still provisions that must be considered such as debt schemes that do not use interest or the practice of usury and only carried out in circumstances emergency and intended for meeting the needs that are important to the community. In addition, although debt instruments have beneficial values for the economy, there are many things that must be considered such as good management of the government, good political conditions, and efficiency and the absence of corruption or other illegal acts. In Islamic fiscal policy, there are various alternative sources of state income that have enormous potential through zakat, infaq, alms, and endowments. In addition, the use of debt instruments can be carried out in accordance with Islamic rules through the concept of mudaraba, musyarakah, and buying and selling business contracts.